Cooperative Learning Model with Process Skills for Mathematics Learning in Elementary School - Kamid, Kamid; Syaiful, Syaiful; Theis, Roseli; Sufri, Sufri; Rohana, Siti (Universitas Pendidikan Ganesha, 2022)
The problem that often occurs in the learning process is the low student learning outcomes. One of the efforts that can be done to overcome these problems is to apply an innovative learning model. One of the learning models that can be implemented in the learning process is the cooperative learning model. This study aims to analyze student responses to the process skills of the jigsaw and STAD learning models in mathematics. This study is research with a quantitative approach and uses a comparative method. The data collection process was carried out using the observation method, with 144 elementary school students as respondents. The data analysis process was carried out descriptively using the SPSS 25.0 application. The results showed that the student's response to the process skills of the learning model in mathematics learning was quite good, judging from the comparison of each student's data between the jigsaw and STAD learning models. So, it can be concluded that there is a relationship and comparison of the two learning models applied in schools. The results of this study are expected to contribute ideas for knowledge and education as well as provide an overview of the learning model and teaching process skills in mathematics subjects.